Linguistische Analyse eines literarischen Textes: Zum Subjekt in der Erzählung Pimeys von Aino Kallas - Järventausta, Marja (Folia Scandinavica Posnaniensia, 2007)
Using a story by the Finnish author Aino Kallas (1878- 1956) as an example, this article addresses the ąuestion whether and to what extent the methodology of linguistic analysis can contribute to the interpretation of literary texts. A closer look at personal- deictic expressions and grammatical subjects in this story shows that such a linguistic analysis of certain stylistic phenomena in a given literary text may support and elucidate the literary interpretation of that text.